Critical Roles of Thioredoxin in Nerve Growth Factor-Mediated Signal Transduction and Neurite Outgrowth in PC12 Cells - Bai, Jie (J Neurosci, 2003)
Thioredoxin (TRX) has a role in a variety of biological processes, including cytoprotection and the activation of transcription factors. Nerve growth factor (NGF) is a major survival factor of sympathetic neurons and promotes neurite outgrowth in rat pheochromocytoma PC12 cells. In this study, we showed that NGF induces TRX expression at protein and mRNA levels. NGF activated the TRX gene through a regulatory region positioned from −263 to −217 bp, containing the cAMP-responsive element (CRE). Insertion of a mutation in the CRE in this region abolished the response to NGF. NGF induced binding of CRE-binding protein to the CRE of the TRX promoter in an electrophoretic mobility shift assay. NGF also induced nuclear translocation of TRX. 2′-Amino-3′-methoxyflavone, an inhibitor of mitogen-activated protein kinase kinase, which is a known inhibitor of NGF-dependent differentiation in PC12 cells, suppressed the NGF-dependent expression and nuclear translocation of TRX. Overexpression of mutant TRX (32S/35S) or TRX antisense vector blocked the neurite outgrowth of PC12 cells by NGF. Overexpression of mutant TRX (C32S/C35S) suppressed the NGF-dependent activation of the CRE-mediated c-fos reporter gene. These results suggest that TRX plays a critical regulatory role in NGF-mediated signal transduction and outgrowth in PC12 cells.